A discourse analysis: The adjacency pairs of analysis on talkshow Youtube present - Suci Cinthia Priliana (UICELL, 2018)
This article entitled A Discourse Analysis : The Adjacency Pairs Analysis on Talkshow Youtube Presents, has one objective that is to find out the type of conversation aspects found in the conversation. The study focuses on 4 aspects of conversation those are adjacency pairs, topic management, preference organization and turn – taking. The main data of the research is a script of interview between presenter Kevin O Rourke and a songwriter Taylor Swift. The data were video and script which took place in a studio on September 1st, 2011 and the duration was 30 minutes. This video was downloaded from http://youtube.com/youtube present/taylor swift/. The video was transcribed into the script and found that there were 12 turns. Then it was analyzed based on theory by Paltridge about conversation analysis. From the data, it was founded that there were 6 adjacency pairs that consisted of 1 pair of greeting - greeting, 4 pairs of assessment – agreement, 4 pairs of question – answer, 1 pair of compliment – acceptance, 1 pair of offering – acceptance and 1 pair of leave taking adjacency pair. 3 topics were found in the conversation, all topics were initiated by the Kevin O Rourke and Taylor Swift only follows. Beside the adjacency pairs, there are 10 preference organizations in the data. Me wanted to describe the types of preference organization into two parts: those are preferred response and dispreferred response. Me only found 10 preferred responses and there was no dispreferred response founded in the data. Preference organization was founded in the data and consists of: Question - Answer 4 pairs, Assessment - Agreement 4 pairs, greeting – greeting 1 pair, compliment – acceptance 1 pair, offering – acceptance 1 pair and leave taking adjacency pair 1 pair. 12 turns were taken by speakers in the conversation, and each speaker took 6 turns.